Możliwości wykorzystania partnerstwa publiczno-prywatnego w podnoszeniu konkurencyjności obszarów metropolitalnych - Filipiak, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents problems of practical use of public-private partnership (PPP) as a tool of realization municipal services in local government. The author presents forms and methods of financing investment programmes in local public sector. She also points benefits and barriers in implementation process of PPP. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 11-22